Inovasi Media Pembelajaran Bottle Colour Sebagai Upaya Peningkatan Keaktifan Belajar dalam Pembelajaran Sejarah - Eksel Yesika Permata; Oka Agus Kurniawan Shavab; Yulia Sofiani (Jurnal Artefak, 2026)
The low level of student engagement in history learning became the background of this study. This research aimed to analyze the effect of the Bottle Colour media on the learning engagement of tenth-grade students at SMAN 4 Tasikmalaya in the 2024/2025 academic year. The study addresses a research gap by integrating Behaviorist Theory into the cooperative learning model Teams Games Tournament (TGT). This research employed a quantitative approach with a quasi-experimental Nonequivalent Control Group design. The sample consisted of class X5 as the experimental group using Bottle Colour media and class X6 as the control group using PowerPoint. Data were collected through questionnaires and analyzed using normality, homogeneity, independent sample t-test, and N-Gain tests. The results showed that Bottle Colour media significantly affected students’ learning engagement. The experimental class average score increased from 52.39 to 73.97, with a significance value of 0.000 < 0.05 and an N-Gain score of 0.6872. Therefore, Bottle Colour media effectively improved students’ engagement in history learning.